Planet Hunters TESS II: findings from the first two years of TESS. Issue 4 (8th December 2020) - Eisner, N L; Barragán, O; Lintott, C; Aigrain, S; Nicholson, B; Boyajian, T S; Howell, S; Johnston, C; Lakeland, B; Miller, G; McMaster, A; Parviainen, H; et al.
ABSTRACT: We present the results from the first two years of the Planet Hunters TESS (PHT) citizen science project, which identifies planet candidates in the TESS ( Transiting Exoplanet Survey Satellite ) data by engaging members of the general public. Over 22 000 citizen scientists from around the world visually inspected the first 26 sectors of TESS data in order to help identify transit-like signals. We use a clustering algorithm to combine these classifications into a ranked list of events for each sector, the top 500 of which are then visually vetted by the science team. We assess the detection efficiency of this methodology by comparing our results to the list of TESS Objects of Interest (TOIs) and show that we recover 85 per cent of the TOIs with radii greater than 4 R⊕ and 51 per cent of those with radii between 3 and 4 R⊕ . Additionally, we present our 90 most promising planet candidates that had not previously been identified by other teams, 73 of which exhibit only a single-transit event in the TESS light curve, and outline our efforts to follow these candidates up using ground-based observatories. Finally, we present noteworthy stellar systems that were identified through the Planet Hunters TESS project.